2016
DOI: 10.1002/hipo.22622
|View full text |Cite
|
Sign up to set email alerts
|

Repetition suppression in the medial temporal lobe and midbrain is altered by event overlap

Abstract: Repeated encounters with the same event typically lead to decreased activation in the medial temporal lobe (MTL) and dopaminergic midbrain, a phenomenon known as repetition suppression. In contrast, encountering an event that overlaps with prior experience leads to increased response in the same regions. Such increased responding is thought to reflect an associative novelty signal that promotes memory updating to resolve differences between current events and stored memories. Here, we married these ideas to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 81 publications
(127 reference statements)
1
20
0
Order By: Relevance
“…While this finding was not expected a priori, it is consistent with the proposal that interactions between midbrain and medial temporal regions are not unique to externally motivated rewards but support encoding and consolidation in general (Lisman et al, 2011). Consistent with this view, midbrain has been shown to interact with hippocampus in encoding tasks that do not involve reward (Duncan et al, 2014;Zeithamova, Manthuruthil, & Preston, 2016), with both background connectivity during encoding (Duncan et al, 2014) and rest connectivity after encoding (Tompary et al, 2015) tracking associative memory. Our findings suggest that midbrain connectivity during reward motivated encoding may be more relevant to overall associative memory than reward modulation of memory and potentially plays a distinct functional role in memory from other reward-related regions.…”
Section: Task Stagesupporting
confidence: 84%
See 1 more Smart Citation
“…While this finding was not expected a priori, it is consistent with the proposal that interactions between midbrain and medial temporal regions are not unique to externally motivated rewards but support encoding and consolidation in general (Lisman et al, 2011). Consistent with this view, midbrain has been shown to interact with hippocampus in encoding tasks that do not involve reward (Duncan et al, 2014;Zeithamova, Manthuruthil, & Preston, 2016), with both background connectivity during encoding (Duncan et al, 2014) and rest connectivity after encoding (Tompary et al, 2015) tracking associative memory. Our findings suggest that midbrain connectivity during reward motivated encoding may be more relevant to overall associative memory than reward modulation of memory and potentially plays a distinct functional role in memory from other reward-related regions.…”
Section: Task Stagesupporting
confidence: 84%
“…Resting state functional connectivity can change on a short time-scale in response to a task (Tambini et al, 2010;Urner, Schwarzkopf, Friston, & Rees, 2013), with learning-related connectivity changes relating to memory performance (Gruber et al, 2016;Murty et al, 2017;Tambini et al, 2010;Urner et al, 2013). During task performance, across-region coupling may change even more rapidly, differentiating between memory task conditions at the order of minutes or even from individual trial to individual trial (Kafkas & Montaldi, 2015;Rissman, Gazzaley, & D'Esposito, 2004;Zeithamova et al, 2012;Zeithamova et al, 2016). For example, Kafkas and Montaldi (2015) showed that hippocampal-VS connectivity was greater during encoding of unexpected versus expected stimuli.…”
Section: Task Stagementioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on August 31, 2020 -Published by learnmem.cshlp.org Downloaded from overlapping information in between item repetitions reduces repetition priming compared with repetition without interleaved related information (Zeithamova et al 2016), which indicates a need to re-parse target information in relationship to other recently experienced, similar information. In the case of L1 target recollections, a related lure is presented between the target's presentation at encoding and that at retrieval.…”
Section: Learning and Memorymentioning
confidence: 99%
“…During encoding, multiple learning leads to decreased activation in stimulus-related cortical regions and the hippocampus when compared to learning once (for reviews, Grill-Spector et al, 2006 ; Segaert et al, 2013 ). The repetition suppression in the hippocampus is confirmed when the single stimuli (e.g., pictures, Suzuki et al, 2011 ; Manelis et al, 2013 ) and stimulus associations are repeatedly presented (e.g., face-name pairs, Rand-Giovannetti et al, 2006 ; Vannini et al, 2013 ; face-scene pairs, Kremers et al, 2014 and object pairs, Zeithamova et al, 2016 ). During retrieval, studies which focus on implicit retrieval suggested that the hippocampal activation increases when subjects retrieve repeated items (vs. new items) by explicit strategy (e.g., Schacter and Buckner, 1998 ; for reviews, see Segaert et al, 2013 ; Kim, 2017 ), but those studies did not directly manipulate retrieval processes to explore the role of the hippocampus for the learning effect.…”
Section: Introductionmentioning
confidence: 95%